Implementation of Problem-Solving Learning Model to Improve Problem-Solving Skills of MAN 1 Kota Gorontalo Students - Pikoli, Masrid; Amu, Siti Fadila Muhtar; Suleman, Nita (Universitas Pendidikan Mandalika, 2024)
This study aims to improve problem-solving skills in thermochemistry material for 11th Grade MIPA (Mathematics and Natural Science) 2 class of MAN (Islamic Senior High School) 1 Kota Gorontalo students. This study is a class action research conducted in two cycles. The subjects of this study were all students of 11th Grade MIPA 2 class of MAN 1 Kota Gorontalo, which amounted to 40 students. Data collection methode include tests and observations, while data analysis involves qualitative descriptive study. Data was obtained from the test results of students' problem-solving skills and the result of observing teacher and student activities through observation sheets. The results show that problem-solving learning model can improve students' problem solving skills, where the ability to understand the problem from 72% in Cycle I increased to 90.8% in Cycle II. The ability to plan problem-solving increased from 73.5% in Cycle I to 87.7% in Cycle II. The ability to execute the plan increased from 69.8% to 86.6% in cycle II, while the ability to rechek increased from 57.5% in Cycle I to 77.7% in Cycle II. Then, teacher activity increased from 65.71% in Cycle I to 85.71% in Cycle II. Moreover, student activity increased from 61.62% in Cycle I to 80.12% in Cycle II.